2021
DOI: 10.1021/acs.langmuir.1c00179
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Reversibility and Structural Stability in Lysozyme Induced by Epirubicin Hydrochloride

Abstract: Herein we report the binding interactions between lysozyme (Lyz) and an anthracycline drug, epirubicin hydrochloride (EPR), through an extensive spectroscopic approach at both ensemble average and single molecular resolution. Our steady-state and time-resolved fluorescence spectroscopy reveals that the drug-induced fluorescence quenching of the protein proceeds through a static quenching mechanism. Isothermal titration calorimetry (ITC) and steady-state experiments reveal almost similar thermodynamic signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Recently, FCS has been utilized to gain insight regarding processes involving the molecular diffusion, complexation, conformational dynamics, and binding affinity of the drug to its targets such as protein, DNA, and so forth with single-molecule resolution. ,,,, It is one of the advanced techniques to estimate the diffusion properties such as the diffusion time (τ D ) and diffusion coefficient ( D t ) of the probe by measuring the fluctuation in fluorescence intensity over time. It is reported that the FCS technique has been employed to evaluate the efficiency of a drug being delivered to a target site, such as DNA. , Here, we have estimated the diffusion coefficient, hydrodynamic radius ( r H ), and binding strength of EPR-WM and EPR-MM DNA systems by monitoring the diffusion of EPR in both bound and free states at very low concentrations (10 nM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, FCS has been utilized to gain insight regarding processes involving the molecular diffusion, complexation, conformational dynamics, and binding affinity of the drug to its targets such as protein, DNA, and so forth with single-molecule resolution. ,,,, It is one of the advanced techniques to estimate the diffusion properties such as the diffusion time (τ D ) and diffusion coefficient ( D t ) of the probe by measuring the fluctuation in fluorescence intensity over time. It is reported that the FCS technique has been employed to evaluate the efficiency of a drug being delivered to a target site, such as DNA. , Here, we have estimated the diffusion coefficient, hydrodynamic radius ( r H ), and binding strength of EPR-WM and EPR-MM DNA systems by monitoring the diffusion of EPR in both bound and free states at very low concentrations (10 nM).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, research has been directed toward the identification and design of site- and sequence-specific DNA-binding small-molecule drugs to make the nucleic acids a new drug discovery target. Most of the anticancer drugs bind to DNA in a more sequence-specific manner through various kinds of noncovalent interaction modes such as external binding with a phosphate backbone, groove binding, and intercalation between base pairs. These types of noncovalent binding modes are reversible and typically preferred over covalent binding, keeping the toxic side effects and drug metabolism in mind. Anthracycline drug epirubicin hydrochloride (EPR, Scheme a) is one of the most imperative anticancer drugs used in the treatment of leukemia, lymphoma, and sarcoma and is reported to be less toxic compared to its parent compound doxorubicin. , In a cancer cell, it localizes inside the nucleus by forming a complex with DNA through an intercalation mode of binding. , This complex prevents topoisomerase II by interfering with protein synthesis, and hence the subsequent DNA replication stops . However, an in-depth elucidation of the sequence-selective binding interaction of EPR with DNA through a systematic study and its binding aspects toward single nucleotide mismatched base pairs containing DNA, which is overexpressed in cancer cells, is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial and biomedical applications of enzymes continue to expand because of their unique catalytic efficiency and selectivity. Many mesophilic enzymes have poor thermal stability and poor retention of their catalytic activity above 50–60 °C, thus limiting their applications when extended use at elevated temperatures is beneficial to increase productivity and decrease bacterial contamination of the industrial processes and when enzyme storage requires a low temperature. Simple and cost-efficient methods to improve enzyme stability are in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…To study the changes in the protein secondary structure at different pH values, CD spectra were tested and analyzed. 42 The positive peak centered at 193 nm and one negative wide peak at 216 nm were observed for pH 6.0 alone (Figure 2a), suggesting that the proportion of every secondary structure is similar. For pH 7.0, a positive peak was observed at 193 nm, and two negative peaks were observed at 209 and 220 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…For (TA/Lyz) n , the conformation of TA was fixed, and checking the conformation of Lyz was very necessary to understand the above diffusion behavior of TA. To study the changes in the protein secondary structure at different pH values, CD spectra were tested and analyzed . The positive peak centered at 193 nm and one negative wide peak at 216 nm were observed for pH 6.0 alone (Figure a), suggesting that the proportion of every secondary structure is similar.…”
Section: Resultsmentioning
confidence: 94%